An analysis of different modalities of bone mineral densitometry evaluation in cage subsidence in anterior cervical discectomy and fusion - Yu, Qingsong; Chen, Jiabao; Wang, Haidong; Ma, Lei (Frontiers in Surgery, 2024)
ObjectiveTo compare the effectiveness of different measurement methods on bone miner density (BMD), including cervical HU of CT, MRI-based cervical vertebral bone quality (C-VBQ), and T value of DEXA, for predicting cage subsidence after single-level ACDF.MethodsThis is a retrospective study, and patients who underwent single-level ACDF from June 2019 to June 2022 were recruited. We collected preoperative total segmental vertebral height (pre-TSVH), cage subsidence height, cervical angle (CA), T1-slope, straight or reverse cervical curvature, mean HU value of C3–7 (C-HU), mean HU of segment (seg-HU), C-VBQ, segmental C-VBQ (seg-VBQ), and total lumbar T value (T value). The variables between the two groups were compared by Student's t test or chi-square test. Logistic regression was used to determine the independent risk factors for subsidence. The ROC curve was used to analyze the predictive efficiency of C-HU, seg-HU, C-VBQ, seg-VBQ and T value for cage subsidence. Finally, the correlations of C-HU, seg-HU, C-VBQ, seg-VBQ, T value and subsidence height were analyzed.ResultsA total of 320 patients were included in this study, and 97 patients (30.31%) had cage subsidence at the last follow-up. The subsidence height was 4.25 ± 0.937 mm in the subsidence group and 1.40 ± 0.726 mm in the nonsubsidence group. There were statistically significant differences between the two groups in bone mineral density-related indexes, including C-HU, seg-HU, C-VBQ, seg-VBQ, and T value (p < 0.05). Logistic regression analysis showed that C-HU was an independent risk factor for vertebral subsidence after single-level ACDF. ROC curve analysis showed that C-HU had the largest AUC of 0.897 (0.862, 0.933) in predicting vertebral subsidence. Correlation analysis showed that C-HU had a high correlation with the T value (r = 0.662, p < 0.001), while C-VBQ had a low correlation with the T value (r = −0.173, p = 0.002), and C-VBQ had a low correlation with subsidence height (r = 0.135, p = 0.016).ConclusionOur study showed that compared with the C-VBQ and T value, C-HU is more effective for predicting cage subsidence after ACDF. Using the segmental index of C-VBQ or HU could not improve predictive effectiveness. C-VBQ may be insufficient in predicting cage subsidence and estimating BMD.